Are DNA repair factors promising biomarkers for personalized therapy in gastric cancer? - Abdel-Fatah, Tarek; Arora, Arvind; Gorguc, Ipek; Abbotts, Rachel; Beebeejaun, Sarah; Storr, Sarah J.; Mohan, Vivek; Hawkes, Claire; Soomro, Irshad N.; Lobo, Dileep N.; Parsons, Simon L.; Madhusudan, Srinivasan (Mary Ann Liebert, 2013)
Chronic inflammation is a driving force for gastric carcinogenesis. Reactive oxygen species (ROS) generated during the inflammatory process generates DNA damage that is processed through the DNA repair pathways. In this study, we profiled key DNA repair proteins (single-strand-selective monofunctional uracil-DNA glycosylase 1 [SMUG1], Flap endonuclease 1 [FEN1], X-ray repair cross-complementing gene 1 [XRCC1], and Ataxia telangiectasia mutated [ATM]) involved in ROS-induced oxidative DNA damage repair in gastric cancer and correlated to clinicopathological outcomes. High expression of SMUG1, FEN1, and XRCC1 correlated to high T-stage (T3/T4) (p-values: 0.001, 0.005, and 0.02, respectively). High expression of XRCC1 and FEN1 also correlated to lymph node-positive disease (p-values: 0.009 and 0.02, respectively). High expression of XRCC1, FEN1, and SMUG1 correlated with poor disease-specific survival (DSS) (p-values: 0.001, 0.006, and 0.05, respectively) and poor disease-free survival (DFS) (p-values: 0.001, 0.001, and 0.02, respectively). Low expression of ATM correlated to lymph node positivity (p=0.03), vascular invasion (p=0.05), and perineural invasion (p=0.005) and poor DFS (p=0.001) and poor DSS (p=0.003). In the multivariate Cox model, high XRCC1 and low ATM were independently associated with poor survival (p=0.008 and 0.011, respectively). Our observation supports the hypothesis that DNA repair factors are promising biomarkers for personalized therapy in gastric cancer. Antioxid. Redox Signal. 18, 2392–2398.